1941
DOI: 10.1002/hlca.19410240102
|View full text |Cite
|
Sign up to set email alerts
|

Etudes sur les matières végétales volatiles XIII. Sur les α‐ et β‐vétivones

Abstract: Etudes SUP les matieres vegetales volatiles XIII1).Sur les a-et p-vetivones par Y. R. Naves e t E. Perrottet. (29. XI. 40.) A . St. Pfau et PI. A . Plattnw ont Ptabli que les essences de v@tiver renferment en proportions dlevkes un mklange de cBtones sesquiterpdniques, a-@thknoldes, bicycliques. Ces auteurs en ont isol@, par l'intermkdiaire des semicarbazones, les K -et P-re'tivones 2). 11s on$ attribut! 21, la P-vPtivone la formule suivante, d'un d6rivP d'un hexahydro-v6tivazul&ne3) 4, :En poursuivant ces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1941
1941
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Relatively low , legume and styrax Very strong , woody , citrus ( nootkatone ), key component of vetiver . Undoubtedly plays the major role in contributing the true odor of vetiver …”
Section: Analytical Aspectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Relatively low , legume and styrax Very strong , woody , citrus ( nootkatone ), key component of vetiver . Undoubtedly plays the major role in contributing the true odor of vetiver …”
Section: Analytical Aspectsmentioning
confidence: 99%
“…Historically, the first constituents isolated from vetiver were obtained by the crystallization of the semi‐carbazone derivatives of components of the ketonic fraction. These pioneering works were conducted in the Givaudan company by Plattner and Pfau and shortly after by Naves and Perrottet . Two purified ketones were isolated by this process, and were named α‐ and β‐vetivones .…”
Section: Eremophilanes and Vetispiranes: The Vetivonesmentioning
confidence: 99%
See 2 more Smart Citations
“…The olfactory properties of 1 and 2 have long been a subject of controversy between fragrance companies. In the early studies, Naves and Perrottet (Givaudan) described 2 as weak, styrax, vegetable-like, while 1 had a characteristic potent and warm vetiver note [5]. In contrast, Maurer (Firmenich) reported that both 1 and 2 were relatively weak and uninteresting [12], while Mookherjee et al (IFF) described 2 as one of the most important contributors to the vetiver odor [13].…”
mentioning
confidence: 97%